THE ARRANGEMENT OF KUTEUI AS A SUBJECT OF CUSTOMARY VILLAGE GOVERNMENT IN THE MANAGEMENT OF COMMUNITY LAND RESOURCES KUTEUI IN THE REGENCY OF REJANG LEBONG - Yamani, M. Yamani; Neta, Yulia; Awanisa, Agsel; Neyasyah, Muhammad Syirazi (Cepalo, 2026)
Kuteui is a customary law community in Rejang Lebong Regency, Bengkulu Province, recognized by the state under Regional Regulation Number 5 of 2018. It possesses customary (ulayat) territory managed according to Rejang customary law. The enactment of the Village Law (Law No. 6 of 2014) provides an opportunity to organize Kuteui as a customary village government with authority to manage its territory. Using an empirical juridical approach and qualitative analysis, this study finds that Kuteui meets the legal requirements for recognition as a traditional village government, including active membership, customary territory, and a functioning customary legal system. The main obstacle is the lack of concrete legal action transferring rights over customary territory from the state, particularly forest areas, to Kuteui.